Penggunaan Warna Semulajadi Dan Teknik Sulaman Tangan Pada Anyaman Tikar Mengkuang Untuk Rekaan Beg Tangan Wanita - Ellyvia Janta, Anak Jeman. (Universiti Malaysia Sarawak (UNIMAS), 2018)
Product production of pandanus ( mengkuang ) is to further enhance the use of nature to produce products such as handbags for women. The leaves are studied and treated to see their suitability as the main ingredient for the design of the bag, as it is a natural substance. Experimentation of color is also done on the ding leaves that have gone through several processes. pandanus ( mengkuang ) leaves are very difficult to produce because of their prickly leaves and their processes are very long. The pandanus ( mengkuang ) leaves are colored using batik colors and natural colors such as turmeric. In order to produce hand-made bag designs made of woven mats. One of the embroidery motifs used is the floral motif.